Implementasi Diversi pada Penyidikan Tindak Pidana Penganiayaan oleh Anak: Diversion Practices in Child Assault Cases at the Investigation Stage - Fathkur Rokhim; Kadi Sukarna; Ani Triwati; Rima Saputri (Universitas Semarang, 2025)
This study aims to analyze the implementation of diversion as a legal mechanism at the investigation stage in handling assault cases committed by children at the Demak Police Resort (Polres Demak). Diversion, as regulated in Law No. 11 of 2012, serves as an alternative dispute-resolution mechanism outside the formal judicial process through a restorative justice approach, thereby requiring the active involvement of offenders, victims, their families, the community, and law enforcement authorities. Employing an empirical juridical method and a case-study approach within the Child and Women Protection Unit (Unit PPA) of Polres Demak, data were collected through interviews and literature review, and qualitatively analyzed using the treatment theory of punishment, restorative justice theory, and Friedman’s legal system theory. The findings reveal that the sentencing framework under the Juvenile Criminal Justice System Law aligns with the treatment theory by prioritizing rehabilitation over retribution. The implementation of diversion by Unit PPA generally reflects restorative justice principles, particularly in terms of objectives and procedural stages. However, at the outcome stage, diversion agreements frequently involve transactional compensation practices that may impose undue burdens on child offenders. The main obstacles stem from societal legal culture, including persistent retributive mindsets, limited public understanding of diversion, and disproportionate compensation demands. This study recommends strengthening legal education and enhancing collaboration between the police, community leaders, and social institutions to improve the effectiveness of diversion. Penelitian ini bertujuan menganalisis implementasi upaya hukum diversi pada tingkat penyidikan dalam penanganan tindak pidana penganiayaan oleh anak di Polres Demak. Diversi sebagaimana diatur dalam UU No. 11 Tahun 2012 merupakan mekanisme penyelesaian perkara anak di luar peradilan dengan pendekatan keadilan restoratif, sehingga memerlukan sinergi antara pelaku, korban, keluarga, masyarakat, dan aparat penegak hukum. Penelitian ini menggunakan metode yuridis empiris melalui studi kasus pada Unit PPA Polres Demak, dengan pengumpulan data melalui wawancara dan telaah pustaka, kemudian dianalisis secara kualitatif menggunakan teori pemidanaan treatment, teori keadilan restoratif, dan teori sistem hukum Friedman. Hasil penelitian menunjukkan bahwa sistem pemidanaan dalam UU SPPA telah sejalan dengan teori pemidanaan treatment karena menekankan pembinaan daripada pembalasan. Implementasi diversi oleh Unit PPA Polres Demak sebagian besar telah mencerminkan prinsip keadilan restoratif, terutama dalam aspek tujuan dan proses. Namun, pada tahap hasil kesepakatan diversi, masih ditemukan praktik ganti rugi yang bersifat transaksional dan berpotensi memberatkan pelaku. Kendala utama berasal dari aspek budaya hukum masyarakat yang masih berpola pikir retributif, kurangnya pemahaman mengenai diversi, dan tuntutan ganti rugi yang tidak proporsional. Penelitian ini menawarkan rekomendasi peningkatan edukasi hukum dan penguatan sinergi antara kepolisian, tokoh masyarakat, dan lembaga sosial guna mengoptimalkan penerapan diversi.